Practice and Principles in Therapeutic Colonoscopy (Springer Berlin Heidelberg, 2018)
This book presents state of the art knowledge and guidance on the use of therapeutic colonoscopy for all of the usual indications, including hemostasis for colorectal bleeding, resection of benign and malignant lesions, and decompression and recanalization of obstructed bowel. Technical aspects are covered in detail, with advice on indications and instrumentation and provision of tips and tricks of proven practical value. With respect to polypectomy, separate chapters focus on technique for pedunculated polyps and the choice between endoscopic piecemeal mucosal resection and endoscopic submucosal dissection for large sessile polyps. The closing chapter looks to the future of therapeutic colonoscopy. The clearly written text is supported by numerous helpful illustrations. Over the years, technological developments have markedly increased the therapeutic, as opposed to the diagnostic, role of endoscopy. This book will be an invaluable aid in clinical practice for all who are involved in the performance of therapeutic colonoscopy.